Some Forms of InvestorRiskTolerance in Investing: Review Theory - Jumadil Saputra (Research Collaboration Community (RCC), 2020)
Investors in investing are always accompanied by a sense of tolerance for the risk of funds invested in an asset. Each investor has a different form of risk tolerance, depending on the function of the utility. This paper aims to conduct a theoretical study of the forms of investor risk tolerance for several utility functions. This study is carried out by reviewing several utility functions which include: square root utility, cubic fraction utility, quadratic utility, exponential negative utility, and logarithmic utility. Based on the results of the study for each of these utility functions, successively obtained risk tolerance in the form of linear, linear, linear, constant, and linear. Linear risk tolerance illustrates that an investor changes the value of his investment in line with changes in the level of risk faced.